Identifikasi Spesies Aphelenchoides pada Benih Padi Varietas Lokal Sumatera Utara Berdasarkan Marka Molekuler - Della Sitanggang; Supramana; Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2026)
The nematode Aphelenchoides besseyi was successfully detected and morphologically identified in the rice seeds of Samosir local varieties, namely ‘Siserang’, ‘Sipining’, ‘Sibandung’, and ‘Saratus Ari’. This study aimed to confirm the identity of Aphelenchoides species using universal primers as markers for the D2-D3 expansion region of the 28S rDNA gene. Nematodes were extracted from the seeds of the North Sumatra local varieties including ‘Siserang’, ‘Sipining’, ‘Sipala’, ‘Sirias’, ‘Sigambiri Merah’, and ‘Sigambiri Putih’. Nematodes from the commercial rice variety ‘Pak Tiwi-1’ was used for comparison. DNA extraction of A. besseyi nematodes was carried out using the Holterman method. The amplification process used universal primers D2A-D3B, producing a DNA fragment of approximately 750 bp. DNA amplification of A. besseyi from the Samosir, Simalungun, and Pakpak Bharat Districts successfully produced DNA fragments of approximately 750 bp. Nematodes obtained from the Siserang, Sigambiri Merah, Sirias, Sigambiri Putih, Sipala, and Sipining varieties showed 99.8%–100% homology with A. besseyi isolates from the Indonesia commercial rice variety, Japan, Brazil, and China.